(untitled) (Journal of Nematode Morphology and Systematics, 2009)
Three new and a known species of Mononchida are described and illustrated from Singapore. Iotonchus darreni sp. n. is characterized by having 1.05-1.19 mm long body; 15-16 x 26-28 μm buccal cavity, with dorsal tooth in the posterior half of stoma; mono-prodelphic genital system; vagina lacking pars refringens; and 10-11 anal body widths long tail. I. singaporensis sp. n. has 1.04-1.23 mm long body; 18-19 x 31-33 μm buccal cavity, with dorsal tooth near its base; monoprodelphic genital system; vagina with distinct pars refringens; and 6.3-8.3 anal body widths long and ventrally arcuate tail. Mylonchulus paraindex sp. n. has 0.71-1.01 mm long body; 10-11 x 18-19 μm buccal cavity, with six rows of denticles and no subventral teeth; mono-prodelphic genital system, with distinct pars refringens vaginae and a short postvulval uterine sac; and conoid, digitate tail. Parahadronchus yuenae Thong, 1971 is redescribed.